Correlation Analysis of Umbilical Cord Blood Metabolic Phenotype and Inflammation in Patients with Gestational Diabetes Mellitus Complicated with Overweight and Obesity. (13th May 2022) - Chen, Qiuling; Li, Wenxia; Deng, Yanxia; Li, Yongqi; Huang, Le; Zhao, Liping; Li, Hua
Abstract : Background . Gestational diabetes mellitus (GDM) is a common metabolic disorder in pregnancy. The incidence rate is increasing year by year, which seriously threatens the safety of maternal and infant. Obesity is a vital factor in inducing GDM. Pregnant women with GDM account for a large proportion of overweight and obese pregnant women. Our study aimed to explore the potential mechanism of differential metabolites on inflammation and find the intervention and management methods for GDM in overweight and obese pregnant women. Methods . Umbilical cord blood samples and placenta were collected from normal weight pregnant women with GDM (control group) and overweight and obese pregnant women with GDM (obesity group) for a comparative study. Serum inflammatory factors IL-10, TNF- α, IL-6, lipopolysaccharide (LPS), and TLR4 expression were detected by ELISA. The expression levels of BCL-2 and caspase-3 were measured by Western blot. TUNEL staining was used to observe the apoptosis of placental villi. KEGG combined with metabolomics was used to compare the differences of metabolic maps between the two groups. Results . Compared with the control group, the level of anti-inflammatory factor IL-10 in the cord blood was decreased in the obesity group, while the levels of proinflammatory factors TNF- α, IL-6, and LPS were increased. In the placental tissues, the obesity group had higher concentrations of LPS, TLR4, and caspase-3 and lower concentration of BCL-2. Placental villi in the obesity group were more likely to undergo apoptosis than the control group. Correlation analysis showed that the above metabolite concentrations were negatively correlated with TNF- α or LPS. Conclusion . Metabolites could control obesity in the process of controlling the occurrence and development of inflammation.